Genetic characterization of Toxoplasma gondii from Brazilian wildlife revealed abundant new genotypes - Vitaliano, S. N.; Soares, H. S.; Minervino, A. H.H.; Santos, A. L.Q.; Werther, K.; Marvulo, M. F.V.; Siqueira, D. B.; Pena, H. F.J.; Soares, R. M.; Su, C.; Gennari, S. M. (Elsevier, 2014)
This study aimed to isolate and genotype T.gondii from Brazilian wildlife. For this purpose, 226 samples were submitted to mice bioassay and screened by PCR based on 18S rRNA sequences. A total of 15 T.gondii isolates were obtained, including samples from four armadillos (three Dasypus novemcinctus, one Euphractus sexcinctus), three collared anteaters (Tamandua tetradactyla), three whited-lipped peccaries (Tayassu pecari), one spotted paca (Cuniculus paca), one oncilla (Leopardus tigrinus), one hoary fox (Pseudalopex vetulus), one lineated woodpecker (Dryocopus lineatus) and one maned wolf (Chrysocyon brachyurus). DNA from the isolates, originated from mice bioassay, and from the tissues of the wild animal, designated as primary samples, were genotyped by PCR-restriction fragment length polymorphism (PCR/RFLP), using 12 genetic markers (SAG1, SAG2, alt.SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L258, PK1, CS3 and Apico). A total of 17 genotypes were identified, with 13 identified for the first time and four already reported in published literature. Results herein obtained corroborate previous studies in Brazil, confirming high diversity and revealing unique genotypes in this region. Given most of genotypes here identified are different from previous studies in domestic animals, future studies on T.gondii from wildlife is of interest to understand population genetics and structure of this parasite.
Keywords: Genetic markers; Genotyping; Isolation; PCR/RFLP; South America; T.gondii